UTEM official visit on green campus - Nor Fadzillah, Zulkipli (2017)
Universiti Malaysia Pahang (UMP) has received a visit from Universiti Teknikal Malaysia Melaka (UTEM), one of the universities in the Malaysian Technical University Network (MTUN) to share experienced and ideas in reforestation campus.